Toyota’s supplier association: a case study - Hines, Peter (Henry Stewart Talks, 2018)
This case study examines Toyota’s supplier association, or kyoho kai, and analyses how the firm significantly outperformed its European rivals. By regularly gathering all the members involved in its supply-chain, Toyota promoted the diffusion of best practices throughout the group and maintained a strong focus on cost and quality.